Ni Foucault ni Lacan. De la Loi, entre éthique et finitude - Thomas Bolmain (Meta: Research in Hermeneutics, Phenomenology and Practical Philosophy, 2014)
After highlighting Foucault’s ambivalent position with regards to psychoanalysis, this paper first shows that Foucault’s critical thought, insofar as it finds its condition of possibility in modern philosophy understood as a theoretical discourse on human finitude, must imperatively be complemented in the vicinity of psychoanalytical praxis-discourse: the ethical and political issue of the finished and desiring subjectivity can thus be examined anew. On the basis of the historicization of the Lacanian Law undertaken in La volonté de savoir, the paper therefore concludes that a philosophical anthropology which is able to heave up to today’s decisive issues for the social critique and the politics of emancipation should build upon the Foucaldo-Lacanian critique of “modern” philosophical anthropology, but should not fear to confront it with radical criticism in return.